STUDY OF SYMPTOMATIC HYPONATREMIA IN ELDERLY PATIENTS - V.PADMA,; DR.SYED MOHAMMED JAVID,; DR.NARENDRAN,; PROF.N.N.ANAND,; DR.KARTHIKEYAN, (International Journal of Pharma and Bio Sciences, 2016)
Hyponatremia is one of the commonest electrolyte disturbances encountered in medical wards and contributes to substantial morbidity and mortality. Therefore, this study was taken up to explore the clinical profile of hyponatremia. This cross sectional study was conducted in a tertiary care hospital with 100 patients. History and clinical examinations were recorded in all patients at admission. History specially included compulsive water drinking and intake of diuretics. Complete hemogram, measurement of fasting blood glucose, urea, and creatinine, lipid profile, {thyroid function tests morning serum cortisol (optional)}, and serum electrolytes were done in every patient. This was followed by a plasma and urinary osmolality determination as well as urinary sodium estimation. In our study total incidence of hyponatremia was 14.3%incidence of symptomatic hyponatremia were 5%,out of 100 patients 24 patients had SIADH(24%) which was the commonest cause of hyponatremia. SIADH and euvolumic hyponatremia formed the largest subgroup in the study. Drugs, especially diuretics such as furosemide and hydochlorothiazide, have also contributed fairly for the cause of hyponatremia these results correlated significantly with other studies